Perspektif Buya Hamka Terhadap Hadisa Misoginis - Aliamran, Sabri (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
The purpose of this paper is to explore Hamka's Hermeneutics towards misogyny hadiths to be considered in the contemporary era, when there are widespread distortions of the understanding of hadith which have nuances of segregation towards women. The method in this research is descriptive qualitative, or literature-based study and not field study. The step in this study was to collect references to hadiths with misogyny nuances in Buya Hamka's essays, which the authors took as primary sources namely, Buya Hamka Talking About Women, Tafsir Al-Azhar, Islamic Studies and as secondary sources such as references from articles, magazines, books related to the topic of discussion. Data analysis techniques namely, reading, analyzing critically and drawing conclusions objectively. The findings in this discussion are, Hamka in understanding hadith misogyny does not only rely on textual hadiths, but with contextual and comprehensive meanings. Furthermore, Hamka, in understanding misogyny traditions, gives privileges to women, not isolates them and demeans them. Instead, it gives women's rights according to the portion of eligibility as women.Keywords: Hamka, Hadith, Gender Equality